Recent tendencies in the development of 'human rights': Axiological and applied aspects - N.V. Bekirov (Ученые записки Казанского университета: Серия Гуманитарные науки)
The occurrence and development of “human rights” was discussed in order to indicate the main prospects of their further role and to evaluate the feasible consequences for the Russian state and legal system. The main tasks were to compare the basic norms of the international law on human rights with the constitutional provisions of Russia, to define human rights as a practical factor and moral value influencing the social progress, to analyze the recent trends in the evolution of the international law on human rights and their impact on the Russian legal policy. The constitutional obligation of the Russian state is to observe and strengthen the rights of every human. Notably, Russia has initiated the development of the international system of human rights. It actively participates in drafting and concluding of many international and regional agreements on human rights, thereby maintaining its strong reputation for acting at the global level. The number of international treaties on human rights ratified by Russia is four times higher than it is on average in the world. However, a recently registered lag in the public awareness of new progressive standards in the field of human rights and freedoms developed at the universal and regional levels may negatively affect both the reputation and practical affairs. Russia needs to constantly monitor the existing international trends in the field of human rights and to adjust them to its domestic legislation and practice, as well as to timely participate in the most relevant international treaties and mechanisms.